2021
DOI: 10.1136/bmjopen-2020-041318
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and use of the DEMQOL suite of instruments in research: a systematic review protocol

Abstract: IntroductionDementia is a public health issue and a major risk factor for poor quality of life among older adults. In the absence of a cure, enhancing health-related quality of life (HRQoL) of people with dementia is the primary goal of care. Robust measurement of HRQoL is a prerequisite to effective improvement. The DEMQOL suite of instruments is considered among the best available to measure HRQoL in people with dementia; however, no review has systematically and comprehensively examined the use of the DEMQO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…DEMQOL-CH (Supplementary Material 1) was developed from the widely used DEMQOL system. 26 DEMQOL-Proxy has been validated extensively. 35,36 However, the researchers found that it did not perform well when completed by care aides without an interviewer.…”
Section: Demqol-chmentioning
confidence: 99%
See 1 more Smart Citation
“…DEMQOL-CH (Supplementary Material 1) was developed from the widely used DEMQOL system. 26 DEMQOL-Proxy has been validated extensively. 35,36 However, the researchers found that it did not perform well when completed by care aides without an interviewer.…”
Section: Demqol-chmentioning
confidence: 99%
“…Generating a mixture of self-and proxy reports of QoL for different residents compromises comparability since proxy-reports are consistently lower than self-reports, and staff and family proxy reports also differ systematically. 26 Therefore, simple QoL proxy assessment is a promising approach that can be validly and reliably completed by direct care staff to give a common metric for residents across dementia severity and measure resident QoL scores over time. 14 Care aides (nursing assistants) are in the unique position of having, through their care contact, the detailed knowledge about residents that is required for valid QoL assessment.…”
mentioning
confidence: 99%
“…Scores range from 31–124, with higher scores indicating a better QoL for the person with dementia. Internal consistency for the measure is α = 0.87–0.92, and test-retest reliability is ICC = 0.67–0.84 [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Should we encounter studies with no English abstract in languages other than those listed, we will further leverage our networks to find a colleague who speaks this language. We have successfully applied this approach in previous literature reviews 43–45. We will exclude qualitative studies, non-empirical work, non-systematic (selective) reviews and studies with a focus on the psychometrical testing of instruments.…”
Section: Methods and Analysismentioning
confidence: 99%
“…We have successfully applied this approach in previous literature reviews. [43][44][45] We will exclude qualitative studies, non-empirical work, non-systematic (selective) reviews and studies with a focus on the psychometrical testing of instruments. We will also exclude studies that are conducted in residential facilities providing care for residents with less complex care needs (assisted living, supportive living, retirement homes, senior housing), day care or night care facilities, hospitals, home care, primary care, care housing or studies that focus on LTC homes that admit primarily younger people.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%